Giving Extra Virgin Olive Oil To Wound Healing (Grade Of Inflammation) In Atopic Dermatitis Patients - Lilik Darwati; Siti Sholikha; Husnul Muthoharoh (Universitas Islam Lamongan, 2021)
Atopic dermatitis (AD) is a chronic and recurrent skin inflammation, accompanied by itching, occurs in certain predilection sites and is based on the presence of an inherited inherited hypersensitivity. This dermatitis is the most common form of dermatitis in infants and children. Other names are atopic eczema, dermatitis eczema, Besnier's prurigo and neurodermatitis. Dermatitis can occur for years, even for life, often recurring and interfering with daily activities due to intense itching. Knowing the effect of giving extra virgin olive oil on wound healing (degree of inflammation) in atopic dermatitis patients, the type of research used was pre-experimental because it revealed a cause-and-effect relationship involving only one group of subjects. so there's no control. strict on variables. The type of research design chosen was The One Group Pratest Posttest, which is an experimental design that was carried out in one group without a comparison group. This model has used a pre-test (pratest) then after being given treatment, a measurement (posttest) is carried out again to determine the consequences of the treatment, so that it can be seen the magnitude of the effect of the experiment. The results of the study can be interpreted that before being given olive oil most (75%) of the respondents had a severe degree of dermatitis and after being given olive oil half (50%) of the respondents had a mild degree of dermatitis, and half (50%) of the respondents had a moderate degree of dermatitis. It can be seen that the Z value is -4.916 with a significance of p = 0.000, so H0 is rejected so that H1 is accepted, which means that there is a difference in the degree of dermatitis before and after being given olive oil. Virgine Olive Oil Can Be Used As A Non-pharmacological Therapy In Overcoming The Degrees Of Atopic Dermatitis Both In Public Health Centers And Networks And In Hospitals